PROGRAM LITERASI AL QURAN DI SEKOLAH (STUDI KASUS DI SD ISLAM AL-AMJAD KOTA MEDAN) - Achyar Zein; Mardianto Mardianto; Hafiz Ariefky (Institut Keislaman Abdullah Faqih (INKAFA) Gresik, 2021)
This research article describes the Qur'an literacy program in schools, where this research was conducted at SD Al-Amjad Medan. This study uses a qualitative method with a descriptive type, namely describing the object of research using data collection techniques using observation, interviews and document-tation, data analysis techniques using data reduction, data presentation and drawing conclusions. The results showed: 1) The implementation of the Al-Qur'an literacy program at SD Al-Amjad Medan was carried out based on Permendikbud Number 23 of 2015 concerning the growth of character which was later developed into the school's vision and mission by prioritizing Islamic values. The implementation of the program is carried out systematically through stages and the wafa method with regular student evaluations. 2) The obstacles to imple-menting the Al-Qur'an literacy program are the first, the low quality of teachers. Second, students who are not disciplined and do not get parental support. Third, time constraints. 3) Efforts to overcome obstacles in the implementation of the Qur'an literacy program, namely by conducting training to improve the quality of teachers, cooperating with parents of students and increasing the duration of implementation in the hope that the implementation of Qur'an literacy can run optimally.Keywords: Al Qur’an Literacy, Quality of Teachers